Increased susceptibility of IDH2-deficient mice to dextran sodium sulfate-induced colitis - Hanvit Cha (Redox Biology, 2017)
Inflammatory bowel disease (IBD) is a group of chronic, relapsing, immunological, inflammatory disorders of the gastrointestinal tract including ulcerative colitis (UC) and Crohn's disease (CD). It has been reported that UC, which is studied using a dextran sodium sulfate (DSS)-induced colitis model, is associated with the production of reactive oxygen species (ROS) and the apoptosis of intestine epithelial cells (IEC). Mitochondrial NADP+-dependent isocitrate dehydrogenase (IDH2) has been reported as an essential enzyme in the mitochondrial antioxidant system via generation of NADPH. Therefore, we evaluated the role of IDH2 in DSS-induced colitis using IDH2-deficient (IDH2-/-) mice. We observed that DSS-induced colitis in IDH2-/- mice was more severe than that in wild-type IDH2+/+ mice. Our results also suggest that IDH2 deficiency exacerbates PUMA-mediated apoptosis, resulting from NF-κB activation regulated by histone deacetylase (HDAC) activity. In addition, DSS-induced colitis is ameliorated by an antioxidant N-acetylcysteine (NAC) through attenuation of oxidative stress, resulting from deficiency of the IDH2 gene. In conclusion, deficiency of IDH2 leads to increased mitochondrial ROS levels, which inhibits HDAC activity, and the activation of NF-κB via acetylation is enhanced by attenuated HDAC activity, which causes PUMA-mediated apoptosis of IEC in DSS-induced colitis. The present study supported the rationale for targeting IDH2 as an important cancer chemoprevention strategy, particularly in the prevention of colorectal cancer.